Designing and Implementing a Curriculum to Support Health Equity Research Leaders: The Interdisciplinary Research Leaders Experience - Gollust, Sarah E.; Call, Kathleen T.; Moon, J. Robin; Cluxton, Bonnie; Bailey, Zinzi (Frontiers in Public Health, 2022)
Health inequities in the United States are well-documented. However, research that is focused on solutions, rather than just describing the problem, and research that is designed explicitly to inform needed policy and practice change, is still too rare. The Robert Wood Johnson Foundation Interdisciplinary Research Leaders (IRL) program launched in 2016 with the goal of filling this gap: to generate community-engaged research to catalyze policy action in communities, while promoting leadership among researchers and community partners. In this paper, we describe the creation and implementation of a curriculum for IRL program participants over the first five years of the program. The curriculum—spanning domains of leadership, policy, communication, community engagement, and research methodologies—was designed to cultivate leaders who use research evidence in their efforts to promote change to advance health equity in their communities. The curriculum components implemented by IRL might be applied to other educational programs or fellowships to amplify and accelerate the growth of leaders nationwide who can use research and action to respond to grave and ongoing threats to community health.